Determination of common peak structure from multiple X-ray photo-electron spectroscopy data sets. Issue 1 (1st January 2021) - Murakami, Ryo; Shouno, Hayaru; Nagata, Kenji; Shinotsuka, Hiroshi; Yoshikawa, Hideki
ABSTRACT: X-ray photo-electron spectroscopy (XPS) peak structure (i.e. peak parameters and the number of peaks) offers critical insights in chemical analysis of materials. Reference XPS spectral data are available for single-phases of compounds, as cited in various research papers and databases. Herein, we consider how individual peak structure varies among different reference spectra for the same single-phase of a compound. We developed a technique that automatically estimates common peak structures from multiple spectral data sets. Specifically, we developed a peak separation method that considers both common peak parameters and measurement-derived fluctuations. The proposed method can uniquely estimate the common peak structure of multiple XPS spectral data sets. For example, we applied the proposed approach to Ti 2p XPS results for T i O 2 from 15 previous reports. In this way, we confirmed that estimated structure has high interpret-ability. Graphical Abstract: uf0001